Atributos físicos, hídricos e químicos de solos em sistemas de produção de morango em Turuçu-RS. - Bamberg, Adilson Luís (2010)
Plowing during soil preparation and the use of fertigation and plastic mulching affects the management of strawberry production systems, resulting in temporal variations of soil physical, hydric and chemical attributes throughout the strawberry production cycle. This work had the objective of assessing and understanding the temporal variations of physical, hydric and chemical attributes during the strawberry production cycle in Turuçu, RS, Brazil, and to identify soil quality indicators of these soils by factor analysis. Soil samples with undisturbed and disturbed structure were collected in the 0,00-0,20m top layer of 15 strawberry production areas at four different times to determine the following variables: aggregate mean weight diameter (MWD), aggregate size distribution, total porosity (TotPOR), macroporosity (MacPOR), microporosity (MatPOR), soil water retention curve, S parameter, available water capacity (CAD), available water capacity considering soil salinity (CADs) particle density (Dp), bulk density (BulkDENS), particle size distribution, organic carbon (CO), total Nitrogen (N), cation exchangeable capacity (CECefective), base saturation (V) and basal respiration (RB). Soil saturation extract was obtained, from which it was determined: pH, electric conductivity (ECs), potassium, sodium, calcium, magnesium, sodium adsorption rate (SAR) and exchangeable sodium percentage (ESP). Moreover, a factor analysis of 12 soil attributes from strawberry production systems was conducted to reduce the total information in few factors. Physical, hydric and chemical attributes of the soil from strawberry production seedbeds were subjected to temporal variations. Soil preparation that was executed for seedbed s construction affected the solid-pores relations, and soil became structurally unstable. With time, soil structure and pore sizes were subjected to significant modifications in the way that the available water capacity was increased, allowing a reduction on the frequency of irrigation events. Concentration of nutrients in the soil saturation extract was diminished during the productive cycle, but it was not enough to forbid soil salinization. Factor analysis resulted in the synthesis of 12 attributes to only three factors: soil aggregation, soil capacity to store water and air in the pores, and soil chemical fertility. Seven attributes (CO, N, MWD, MacPOR, CAD, V, and pH) that compose the three yielded factors were selected as soil quality indicators in strawberry production areas in the region of Turuçu, RS, Brazil. In general, it can be affirmed that the soils involved on strawberry production in Turuçu, RS, Brazil had improved their physical, chemical and hydric conditions at the end of production cycle.